2001
DOI: 10.1097/00007890-200103150-00011
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis After Renal Transplantation: Single Center Experience

Abstract: Time since transplantation and cumulative prednisolone doses were significantly higher in patients who had osteoporosis of the lumbar vertebrae (P=0.06 and 0.034, respectively). Logistic regression analysis revealed that cumulative prednisolone dose was the only significant predictor of low vertebral BMD (P=0.02, r=0.33). For the neck of the femur, high blood urea nitrogen and low Mg levels were found to be the predictors of low bone density (P=0.002 and 0.04, respectively). Although parathyroid hormone levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 9 publications
1
20
0
2
Order By: Relevance
“…Length of dialysis was not associated with the severity of BMD loss in kidney transplant patients [15, 20, 28, 33, 39,43,44,45], although one study reported a significant correlation between T scores and dialysis duration for the femoral neck and radius but not the spine [37]. Similarly, kidney function in kidney transplant patients was not associated with BMD [25, 30, 31, 33, 39, 40, 44, 45].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Length of dialysis was not associated with the severity of BMD loss in kidney transplant patients [15, 20, 28, 33, 39,43,44,45], although one study reported a significant correlation between T scores and dialysis duration for the femoral neck and radius but not the spine [37]. Similarly, kidney function in kidney transplant patients was not associated with BMD [25, 30, 31, 33, 39, 40, 44, 45].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, kidney function in kidney transplant patients was not associated with BMD [25, 30, 31, 33, 39, 40, 44, 45]. …”
Section: Resultsmentioning
confidence: 99%
“…Both, ciclosporine and tacrolimus use have been linked to osteoporosis in clinical studies, 33,34 and progression of bone loss with calcineurin inhibitor monotherapies has been demonstrated in rodent models. 35,36 Despite these findings, population-based studies that have focused on fracture risk could not establish an association between use of calcineurin inhibitors and fracture risk.…”
Section: Post-transplant Changes In Bonementioning
confidence: 99%
“…In patients with renal transplants, in addition to known risk factors for bone loss in healthy populations, other abnormalities could negatively affect the bone metabolism, including the pretransplantation renal osteodystrophy, persistent hyperparathyroidism, and use of immunosuppressive drugs (5). The role of glucocorticoids-induced osteoporosis is well documented in many series (6), and there is much evidence that cyclosporin A (CsA) could increase bone resorption as a result of increased osteoclast activity (7,8).…”
mentioning
confidence: 99%